2017
DOI: 10.9744/jmk.19.2.112-117
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Knowledge Sharing in Mediating the Effect of Self-Efficacy and Self-Leadership Toward Innovative Behavior

Abstract: This research is to investigate the correlation between self-efficacy, self-leadership, and knowledge sharing as observed in the innovative behavior of Endek weaving small enterprise in Bali. Innovation is an interesting issue in SMEs, due to its sustainability efforts of the business. Endek weaving is one unique product that has social and economic value. The unit of analysis is Endek weaving small enterprise in Klungkung, a regency located in the east area of Bali, as it is the center production of Endek wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
(20 reference statements)
3
9
0
3
Order By: Relevance
“…They determined that knowledge sharing functioned as a transfer between perceived SE and employee job performance. Similarly, Widyani et al (2017) found that knowledge sharing operated as a mediator between SE and employee innovative job behaviour because a person with confidence in their own efficacy and the perceived knowledge sharing atmosphere among staff in the workplace or organisation enhance effective performance. According to their study, when a knowledge sharing variable was examined as a mediator, employee job performance could be predicted with greater significance.…”
Section: Hypothesesmentioning
confidence: 98%
“…They determined that knowledge sharing functioned as a transfer between perceived SE and employee job performance. Similarly, Widyani et al (2017) found that knowledge sharing operated as a mediator between SE and employee innovative job behaviour because a person with confidence in their own efficacy and the perceived knowledge sharing atmosphere among staff in the workplace or organisation enhance effective performance. According to their study, when a knowledge sharing variable was examined as a mediator, employee job performance could be predicted with greater significance.…”
Section: Hypothesesmentioning
confidence: 98%
“…Karena mereka merasa kurang mampu dalam menyelesaikan tugas maupun pembelajaran yang diberikan di studi S2 nya nanti. Seseorang dengan self-efficacy rendah menganggap dirinya pada dasarnya tidak mampu melakukan segalanya (Widyani, Sarmawa, & Dewi, 2017). Individu dengan efikasi diri rendah cenderung menghindari hal-hal yang sulit (Sudjarwo, Wahyudin, & Sudarma, 2019).…”
Section: Pengaruh Self Efficacy Terhadap Minat Melanjutkan Studi S2 Pada Mahasiswa Prodi Pendidikan Administrasi Perkantoran Universitas unclassified
“…(2016) pada 327 karyawan hotel di Malaysia dan menemukan dampak signifikan berbagi pengetahuan terhadap perilaku inovatif. Widyani, et. al.…”
Section: Teoriunclassified